Papanicolaou tests (Pap smears) from a woman's perspective (Research, Society and Development, 2022)
This study seeks to attribute and correlate the importance of clinical Papanicolaou tests, also known as Pap smears, for both women's physical and mental health. Emphasis was given to woman's awareness and feelings related to these exams, and to educational interventions to promote greater awareness. Objectives: To emphasize women’s perspectives on the importance of Pap smears as a method for preventing and diagnosing neoplastic diseases and HPV. Specifically, the objective of this study was to emphasize women’s experiences, exam techniques, exam adherence levels, and orientations related to how the exam can aid in preventative care. This systematic review was developed following PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines. The inclusion criteria analyzed studies focused on the Pap smear from the female perspective, elucidating the feelings in the practice of the examination and interventions for cervical cancer screening. The analysis and screening of the studies indicated 29 articles with eligible potential. Of these, 23 were included in the study, 12 literature reviews, 9 original articles and 2 observational studies.We observed a general lack of awareness and guidance on the importance of Pap smears, along with infrequent testing levels, that could otherwise lead to diagnosing common and widespread diseases in adolescent and elderly women. Feelings of fear and shame were common barriers to examination adherence, meaning that educational interventions are necessary, along with other informative and qualitative actions.